Teachers’ views of their school climate and its relationship with teacher self-efficacy and job satisfaction - Aldridge, Jill; Fraser, Barry (2015)
The purpose of this study, in part, was to confirm the factor structure of the School-Level Environment Questionnaire, which assesses six school climate factors that can be considered important for improving schools. The study also tested a research model of the relationships between the school climate, teachers’ self-efficacy and job satisfaction. The participants included 781 Western Australian high-school teachers in 29 schools. When the data were analysed by means of structural equation modelling, teacher self-efficacy and teacher job satisfaction were both related to school climate dimensions and there was also a relationship between teacher self-efficacy and job satisfaction. These results provide practical information for improving school climate and suggest that it is worthwhile for school principals to consider factors within the school climate and how they might be enhanced.